PROFIL KEMAMPUAN BERPIKIR KRITIS SISWA PADA POKOK BAHASAN SENYAWA KARBON KELAS XI SMA NEGERI 2 MRANGGEN - Setyawan, Joko; Patonah, Siti (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
This study aims to determine the profile of critical thinking ability of high school students on hydrocarbon material. This research was carried out at SMA Negeri 2 Mranggen for the 20221/2022 academic year. The subjects of this study were students of class XI MIPA 1 with details of 10 male students and 20 female students. The data collection technique uses a description test instrument of 10 questions representing 5 critical thinking indicators, namely providing simple explanations (elementary clarification), building basic skills (basic support), concluding (inference), providing further explanations (advanced clarification), developing strategies and tactics (strategy and tactics). The results showed that 13% of students have very high critical thinking ability, 30% of students have high critical thinking ability, 40% of students have medium critical thinking ability, 10% of students have low critical thinking ability and 7% of students have very low critical thinking ability. This can be interpreted to mean that students already have good critical thinking skills. Keywords: Hydrocarbons, Critical Thinking Ability, Profile